Transcriptome and WGCNA reveals the potential genetic basis of photoperiod-sensitive male sterility in soybean - Yuhua Yang; Suqin He; Lihong Xu; Minggui Wang; Shuichun Chen; Zhiyuan Bai; Tingting Yang; Bo Zhao; Lixiang Wang; Haiping Zhang; Jiangjiang Zhang; Ruijun Zhang (BMC Genomics)
Abstract Background Soybean (Glycine max (L.) Merr.) is a crucial crop due to its high plant protein and oil content. Previous studies have shown that soybeans exhibit significant heterosis in terms of yield and protein content However, the practical application of soybean heterosis remains difficult, as the molecular mechanisms underlying photoperiod-sensitive genic male sterile (PGMS) is still unclear. Results This study characterized the PGMS line 88-428BY, which is sterile under short-day (SD) conditions and fertile under long-day (LD) conditions. To elucidate the genetic basis for this trait, we collected anthers, from 88-428BY under SD and LD conditions at three developmental stages, resulting in the identification of differentially expressed genes (DEGs) (2333, 2727 and 7282 DEGs, respectively) using Illumina transcriptome analysis. Using Gene Ontology and Kyoto Encyclopedia of Genes and Genomes pathway analyses, we fund that among the DEGs, enriched genes were associated with photoperiod stress, light stimulus, oxidation-reduction processes, multicellular organism development and protein phosphorylation. Additionally, weighted correlation network analysis identified four modules (blue, brown, red, and yellow) that were significantly correlated with PGMS, revealing co-expressed hub genes with potential regulatory roles. Functional annotation of 224 DEGs with|KME| >0.9 across the four modules in seven databases highlighted their involvement in light stimulus, oxidation-reduction processes, multicellular organism development, and protein phosphorylation, suggesting their importance in soybean PGMS. By integrating fertility-related genes previously identified by other studies with the DEGs from our analysis, we identified eight candidate genes associated with the photosensitive sterility in soybeans. Conclusions This study enhances the understanding of PGMS in soybean and establishes the genetic basis for a two-line hybrid seed production system in soybean.